ANALISIS PENERAPAN KRITERIA MALCOLM BALDRIGE (MBCfPE) TERHADAP KUALITAS KINERJA DI KSPPS BMT DAS PURBALINGGA - Dwi Retno Ardani; Hawin Mu’alif Maulana; Nabila Khairunnisa Azhar; Yoiz Shofwa Shafrani (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2025)
This study aims to analyze the implementation of the Malcolm Baldrige Criteria for Performance Excellence (MBCfPE) in enhancing performance quality at KSPPS BMT DAS Purbalingga, a sharia microfinance institution in Indonesia. Using a descriptive quantitative approach, the study assesses seven dimensions of MBCfPE—Leadership, Strategic Planning, Customer Focus, Measurement, Knowledge Management, Workforce Focus, Process Management, and Results. The findings reveal that BMT DAS Purbalingga achieved an overall score of 830, categorizing it as a "Benchmark Leader" under the MBCfPE framework. The highest performance was recorded in the "Customer and Market Focus" category with a score of 88.23%, reflecting the organization's strong customer orientation and service quality. However, the "Measurement, Analysis, and Knowledge Management" dimension scored the lowest (77,77%), indicating room for improvement in strategic data analysis and knowledge utilization. These results suggest that the adoption of MBCfPE has positively influenced institutional performance, positioning KSPPS BMT DAS as a model for excellence in the Islamic microfinance sector. The research contributes to existing literature by providing empirical evidence on MBCfPE application in a sharia cooperative context and supports prior findings on the framework’s versatility across industries.